The Digital Economy is The Basis For Forming A Favorable Investment Environment - Nishonqulov Shohruhxon Farxodjon Ogli; Rajabboyev Botir Odil Ogli (Genius Publishing Group, 2021)
Several factors affect the development of the country's economy. At present, investments are considered as the basis for economic development. As the volume of investments in the country's economy increases, so does the economy. On investment, the President of the Republic of Uzbekistan Shavkat Miromonovich Mirziyoyev said: “World experience shows that the country that pursues an active investment policy has achieved sustainable economic growth. Therefore, it is no exaggeration to say that investment is the driver of the economy, in Uzbek, the heart of the economy. Along with investment, new technologies, advanced experience, highly qualified specialists will come to various industries and regions, and entrepreneurship will develop rapidly
Keywords: investment; innovation; climate; digital technology